Target-activated cascaded digestion amplification of exonuclease III aided signal-on and ultrasensitive fluorescence detection of ATP. (6th February 2018) - Leng, Xueqi; Li, Rongguo; Wang, Yu; Wu, Yunping; Tu, Yuqin; Pei, Qianqian; Cui, Xuejun; Huang, Jiadong; Liu, Su
Abstract : In this work, a rapid, one-step and ultrasensitive signal-on fluorescence sensing for the detection of adenosine triphosphate (ATP) based on target-activated cascaded digestion amplification with Exo III aid was developed. Abstract : In this work, a rapid, one-step and ultrasensitive signal-on fluorescence sensing for the detection of adenosine triphosphate (ATP) based on target-activated cascaded digestion amplification with Exo III aid was developed. Our strategy integrates the target-activated cascaded digestion amplification with Exo III assistance into a signal-on fluorescence sensing platform. This advance greatly enhances the specificity and significantly improves the sensitivity for ATP detection. Specifically, an arch probe containing an anti-ATP aptamer (Apt) and a trigger probe (T) is used for recognizing the target. In the presence of ATP, the cascaded digestion amplification with the help of Exo III was activated, generating a remarkably strong signal-on fluorescence response. Our strategy features several virtues. First, the background signal is effectively eliminated owing to the specially designed hairpin probes (one is named HAP, the other is named MB short for molecular beacon) successfully avoiding the effect of Exo III. Second, the combination of target-activation with Exo III-aided cascade digestion amplification is integrated with fluorescence sensing, affording high specificity and ultrasensitive detection of ATP. Third, our method achieved the reliable and accurate detection of ATP in human serum. Furthermore, under optimized conditions, the results suggest that the proposed fluorescence sensing exhibits excellent specificity and ultrasensitivity toward ATP with the limit of detection as low as 0.63 pM and the broad analytical range from 1 pM to 1.0 × 10 5 pM. This target-activated cascaded digestion amplification with Exo III assistance combined with the fluorescence sensing strategy paves a luciferous and practical way for detecting ATP and other analytes with trace amounts in bio-analysis and clinical biomedicine.